1999
DOI: 10.1177/000348949910800507
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Application of a Protocol for Selective Nonsurgical Management of Suspected Orbital Subperiosteal Abscesses in Children

Abstract: Goodwin et al (1982) and Souliere et al (1990) have proposed a protocol for the selective nonsurgical management of suspected orbital subperiosteal abscesses. This protocol has been routinely applied by the Temple Pediatric Otolaryngology and Ophthalmology services since 1990. During this period, children with computed tomography and physical examination findings consistent with orbital subperiosteal abscesses and visual acuity better than 20/60 were treated with intravenous antibiotics rather than immediate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
3
7
1
Order By: Relevance
“…Table 3 (available online at www.pidj.com) summarizes the epidemiologic and management information from case series published since 1987 of children with orbital cellulitis [5][6][7][8][9][10][11][12][13][14] and with orbital subperiosteal abscesses. 7,11,[15][16][17][18][19][20][21][22][23] Among the 594 cases of orbital cellulitis summarized between 1890 and the mid-1970s (with a few extending into the 1980s), the estimated mean age was 7.4 years, quite similar to our series. 4 The mean ages of 11 series of orbital cellulitis with subperiosteal abscess ranged from 5.5 to 9 years.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Table 3 (available online at www.pidj.com) summarizes the epidemiologic and management information from case series published since 1987 of children with orbital cellulitis [5][6][7][8][9][10][11][12][13][14] and with orbital subperiosteal abscesses. 7,11,[15][16][17][18][19][20][21][22][23] Among the 594 cases of orbital cellulitis summarized between 1890 and the mid-1970s (with a few extending into the 1980s), the estimated mean age was 7.4 years, quite similar to our series. 4 The mean ages of 11 series of orbital cellulitis with subperiosteal abscess ranged from 5.5 to 9 years.…”
Section: Discussionsupporting
confidence: 79%
“…4 The mean ages of 11 series of orbital cellulitis with subperiosteal abscess ranged from 5.5 to 9 years. 7,11,[15][16][17][18][19][20][21][22][23] The striking male preponderance that we observed with orbital cellulitis (73%) and with subperiosteal abscess (75%) has also been seen in most other cases series that provided gender-specific data. 7,10,[13][14][15][16][17][18][21][22][23] Overall, the male:female ratios across these case series suggest that orbital cellulitis in childhood is at least twice as common among males as females.…”
Section: Discussionmentioning
confidence: 53%
“…Some argue that an initial trial of intravenous antibiotics is warranted, reserving surgical treatment for patients who do not respond to antibiotic therapy, whereas others believe that immediate surgical drainage of the abscess and infected sinuses is required. [2][3][4][5][6][17][18][19][20] Regardless of whether surgical intervention is pursued or not, the treatment of the concurrent sinusitis is integral to the management of orbital subperiosteal abscesses. Although broad-spectrum antibiotics are always used in the initial management of the subperiosteal abscess, the use of corticosteroids to treat the orbital subperiosteal abscess has not been well investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical drainage may be necessary in patients not improving with antibiotics alone, in patients with impending visual loss, or in patients with concurrent cavernous sinus or intracranial involvement. [3][4][5][6] Because successful management of the adjacent sinusitis is paramount in facilitating the resolution of the subperiosteal abscess, any therapy that aids the treatment of the sinusitis may also have a beneficial effect in the treatment of the subperiosteal abscess. A number of studies in the medical literature have reported increased levels of a variety of inflammatory cytokines in the sinonasal mucosa of patients with sinusitis.…”
mentioning
confidence: 99%
“…Thus, absence of a definite abscess on CT should not preclude surgical drainage in the face of progression of orbital signs and symptoms. 17 A homogeneous opacity on the scan -i.e. the appearance of cellulitis -may be either caused by cellulitis alone or may indicate early abscess formation.…”
Section: Discussionmentioning
confidence: 99%